PENGELOLAAN KONFLIK DAN KOLABORASI DI PERBATASAN LAUT : PERSPEKTIF INDONESIA TERHADAP KETEGANGAN DAN KESEPAKATAN MARITIM DENGAN CHINA - Samsul Bahri Wahidun; Edy Sulistyadi, Buddy Suseto (CV. ADIBA AISHA AMIRA, 2025)
Tensions at Indonesia's maritime border have escalated in October 2024 after a China Coast Guard (CCG) vessel entered Indonesia's jurisdiction, disrupting oil and gas exploration activities by PT Pertamina East Natuna. Indonesia responded with firm measures, including Bakamla patrols and diplomatic protests based on UNCLOS 1982. On the other hand, in November 2024, the two countries signed a Memorandum of Understanding (MoU) for joint maritime development as an effort to ease tensions while creating strategic economic opportunities. The purpose of this journal is to analyse conflict management and collaboration in the North Natuna Sea border between Indonesia and China. The results show that conflict management requires a balance between a realist approach to defend sovereignty and a liberal institutionalism approach to capitalise on opportunities for cooperation. Thus, recommendations are given to increase defence capacity, align cross-sector policies and strengthen bilateral and regional relations to create stability in the North Natuna Sea region.